PROBLEMS OF DISPUTE RESOLUTION REGIONAL CHIEF ELECTION (GOVERNOR, REGENTS AND MAYOR) - Esti Ningrum; Jawade Hafidz (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
The aim of research conducted in this study, is to analyze the problems of the settlement of disputes local election. The problems of settlement of disputes in the implementation of local elections is problematic power of the judiciary in resolving disputes elections daerahmatika power of the judiciary in resolving disputes local elections, and Problems In Dispute Settlement local elections which disputes the results of the local elections of powers MA into the power of the Court, power in the State Administrative Court judge Decision Peneyelnggara local elections, the power of the General Court in dealing with criminal abuses Daeran elections and enforcement of the code of conduct by the Honorary Board of the General Election Organizer.